Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1002/(sici)1096-9896(199606)179:2<157::aid-path557>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Thevhl Gene Is Associated Exclusively With the Development of Non-Papillary Renal Cell Carcinomas

Abstract: To define the possible role of the VHL gene in the development of sporadic renal cell carcinomas, 91 different parenchymal tumours of the kidney have been investigated for mutation of the VHL gene by single strand conformation polymorphism (SSCP) and/or heteroduplex (HD) techniques. Chromosome 3p deletion was detected in 98 per cent of non‐papillary renal cell carcinomas and in 25 per cent of chromophobe renal cell carcinomas. In 22 of the 43 non‐papillary renal cell carcinomas, abnormally migrating DNA bands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 9 publications
2
33
0
1
Order By: Relevance
“…However, male and female F344 rats both had elevated 8-hydroxydeoxyguanosine levels in the kidney and increased Sphase labeling after up to 13 wk of treatment (28). These data, the present report, and previous work indicating that both male and female rats develop renal tumors suggest that a2u-globulin accumulation is not related to renal tumor development (12,13,28). The droplets that accumulate in association with bromate treatment are associated with bromate-induced oxidant damage and not a2u-globulin nephropathy.…”
Section: Resultssupporting
confidence: 59%
“…However, male and female F344 rats both had elevated 8-hydroxydeoxyguanosine levels in the kidney and increased Sphase labeling after up to 13 wk of treatment (28). These data, the present report, and previous work indicating that both male and female rats develop renal tumors suggest that a2u-globulin accumulation is not related to renal tumor development (12,13,28). The droplets that accumulate in association with bromate treatment are associated with bromate-induced oxidant damage and not a2u-globulin nephropathy.…”
Section: Resultssupporting
confidence: 59%
“…32 The majority of clear-cell RCCs have a loss of chromosome 3p and inactivation of the VHL gene located on 3p25. 33 As a proof-of-concept of the oncogenic-signature approach, we wanted to determine whether sets of genes whose expression is reported to be modified by VHL in cell-line studies 34 could also be detected as misregulated in the geneexpression profiles of clear-cell RCCs. Identification of a downregulated VHL signature in clear-cell RCC would validate the use of literature-curated gene sets to identify misregulated signal-transduction pathways in RCC.…”
Section: Detection Of Oncogenic Pathway In Rccmentioning
confidence: 99%
“…Mutations in VHL, loss of heterozygosity and imprinting were identified in about 70% of sporadic clear-cell RCCs, supporting an earlier hypothesis. 4 However, studies of other hereditary RCC genes found either a small number of or no mutations in the sporadic tumours of subtypes, for example, the MET proto-oncogene for hereditary papillary RCC type 1, 5,6 the BHD gene for Birt-Hogg-Dubé syndrome (characterized by a spectrum of RCC, but freCombining differential expression, chromosomal and pathway analyses for the molecular characterization of renal cell carcinoma …”
mentioning
confidence: 99%
“…The VHL gene, a putative tumour suppressor gene, has already been cloned from the chromosome 3p25.3 region. Its inactivation by mutation occurs in about 50% of sporadic nonpapillary RCCs (Gnarra et al, 1994;Kenck 1996). Cytogenetic analysis of sporadic and hereditary nonpapillary RCCs has also revealed trisomy or partial trisomy of chromosome 5 in about 50% of cases with the smallest overlapping region of duplication for chromosome 5q22-qter region.…”
Section: Introductionmentioning
confidence: 99%